Analysis of 21st-century skills through science literacy in fifth grade science teaching at SDN Lebbek 1 - Maghfiroh, A’as; Maharani, Viza; Setyawan, Agung (ARKA INSTITUTE, 2022)
The purpose of this research to obtain information on the extent to which 21st century skills are improved through scientific literacy. The problem in this research is